What Can International Cricket Teach Us About the Role of Luck in Labor Markets? - Aiyar, Shekhar (IMF Working Papers; Working Paper ;, 2010)
How important is luck in determining labor market outcomes? We address this question using a new dataset of all international test cricketers who debuted between 1950 and 1985. We present evidence that a player's debut performance is strongly affected by an exogenous source of variation: whether the debut series is played at home or abroad. This allows us to identify the role of luck - factors unrelated to ability - in shaping future career outcomes. We find that players lucky enough to debut at home perform significantly better on debut. Moreover, debut performance has a large and persistent impact on long run career outcomes. We also make headway in empirically distinguishing between competing explanations for why exogenous initial conditions exercise a persistent impact on career performance.